Acupuncture as an intervention procedure in Physiotherapy (Cuestiones de Fisioterapia, 2005)
Acupuncture is a therapeutic practice with origin on Traditional Chinese Medicine. Physiotherapy has to look around it and to be conscious of other treatment options, based on the traditional medicines, which with the enough investigation could be adapted and joined to its own tools. Thus, acupuncture can be considered, from the western point of view, a physical therapy which physiological substratum involves the participation of the nervous system by means of reflect mechanisms. Nowadays, it is a practice without official qualifications. Acupuncture presents a legal gap in its exercise regulation. Nevertheless, recent educational adjustments can produce changes about acupuncture training professional character. Bibliographical review, data base consultation and information withdrawal by means of interviews and surveys were used. The selected sample consisted of 76 participants, 27 physiotherapists, 27 nurses and male nurses, and 22 doctors. Four of the five acupuncturists interviewed were physiotherapists and the other was doctor.